An unlikely Christian humanist: how Bess of Hardwick (ca. 1527-1608) answered "the woman question" - LaBouff, Nicole (The sixteenth century journal, 2016)
This article reexamines the intellectual and religious inclinations of Elizabeth Talbot, Countess of Shrewsbury, or "Bess of Hardwick." Popular accounts emphasize her wealth, strong-willed character, staunch Protestantism, and dynastic ambitions. This study revises common assumptions about her character using evidence from a set of embroidered wall hangings Bess owned and designed. Their iconography reveals that she studied Boccaccio's Famous Women, and linked it to other texts in formal comparisons. Bess's textile furnishings reveal that she was prepared to weigh in on such topics as female virtue and soteriology in ways that were empowering for her as a woman, a scholar, and a Christian. These objects demonstrate Bess's notational habits, preparatory methods for dialogue, and sophisticated understanding of iconography. Bess was a product of the same Christian humanist culture as many of her elite contemporaries, and it was her sharp intellect--not her marital pedigree--that helped her win their praise.